2017
DOI: 10.1021/acschemneuro.6b00358
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam Inhibits Electrically Evoked and Tonic Dopamine Release in the Nucleus Accumbens and Reverses the Effect of Amphetamine

Abstract: Diazepam is a benzodiazepine receptor agonist with anxiolytic and addictive properties. Although most drugs of abuse increase the level of release of dopamine in the nucleus accumbens, here we show that diazepam not only causes the opposite effect but also prevents amphetamine from enhancing dopamine release. We used 20 min sampling in vivo microdialysis and subsecond fast-scan cyclic voltammetry recordings at carbon-fiber microelectrodes to show that diazepam caused a dose-dependent decrease in the level of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 46 publications
5
23
0
Order By: Relevance
“…Although microdialysis studies show a net reduction in extracellular DA concentration, the temporal resolution provided by this technique makes it difficult to discern whether a reduction in the amplitude of transient release events contributes to this effect. Additionally, a recent FSCV study demonstrated that BZPs decrease electrically evoked DA release in the NAc of anesthetized rats (Gomez-A et al, 2017). Our study builds upon these data by demonstrating the effects of diazepam on naturally occurring accumbal transient release events in the awake and freely moving animal.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Although microdialysis studies show a net reduction in extracellular DA concentration, the temporal resolution provided by this technique makes it difficult to discern whether a reduction in the amplitude of transient release events contributes to this effect. Additionally, a recent FSCV study demonstrated that BZPs decrease electrically evoked DA release in the NAc of anesthetized rats (Gomez-A et al, 2017). Our study builds upon these data by demonstrating the effects of diazepam on naturally occurring accumbal transient release events in the awake and freely moving animal.…”
Section: Discussionsupporting
confidence: 58%
“…It is possible that the electrophysiological results represent a disinhibition of DA neural activity in the VTA (O'Brien and White, 1987;Tan et al, 2010), which increases both the frequency and amplitude of accumbal transient release events. By contrast, the microdialysis results (Zetterström and Fillenz, 1990;Invernizzi et al, 1991;Finlay et al, 1992Finlay et al, , 1995Takada et al, 1993;Murai et al, 1994;Dazzi et al, 1995;Hegarty and Vogel, 1995;Motzo et al, 1997;Yoshida et al, 1999;Bentue-Ferrer et al, 2001;Rada and Hoebel, 2005;Gomez-A et al, 2017) and the recent anesthetized FSCV study (Gomez-A et al, 2017) might represent a localized suppression of accumbal DA release events. However, it should also be noted that the aforementioned electrophysiological studies identified dopamine neurons solely using electrophysiological criteria-which is now considered insufficient to determine whether a recorded unit is DAergic or GABAergic (Ungless et al, 2004;Ungless and Grace, 2012).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There are some reports of non-GABA A receptor occupancy (5HT, D2) by diazepam (Saner and Pletscher, 1979 ; Gomez et al, 2017 ; van der Kooij et al, 2018 ) raising the possibility that the effects we observed could be mediated via non-GABAergic mechanisms. However, this is unlikely to explain our results given that we observed effects at therapeutic doses of diazepam and that GABAergic networks are a crucial substrate of response inhibition (Nicholson et al, 2018 ).…”
Section: Discussionmentioning
confidence: 65%
“…FSCV is able to measure variations in dopamine concentration with high temporal and spatial resolution (Yorgason et al, 2011). Therefore, it provides information about how fast dopamine is released from and reuptaked to synaptic terminals, which is very important to study effects of drugs of abuse (Gomez-A et al, 2017;Fawaz et al, 2009).…”
Section: Fast-scan Cyclic Voltammetrymentioning
confidence: 99%